Exploring college students’ acceptance and attitude toward the LGBT community - Kamarudin, Aisyah Sakinah; Ahmad, Roslee; Yusoff, Mohd Nasir Che Mohd; Sawai, Rezki Perdani; Mahyuddin, Muhamad Khairi; Hisham, Hizral Tazzif (International Journal of Psychosocial Rehabilitation, 2020)
The aims of this study were to examine the acceptance and attitude of Malaysia undergraduate college student’s toward LGBT community. This study was conducted toward 120 college students’ based on random sampling method. These instruments were adapted from Acceptance and Action Questionnaire - Stigma (AAQS) questionnaire developed by Levin et al. (2014). Heterosexual Attitudes Towards Homosexuality (HATH) Scale developed by Larsen et al. (1980) with Cronbach alpha was 0.84. Data collected were analyzed using Statistical Package for Social Science (SPSS) version 23. The analysis used statistic inference using correlation and t-test. Results showed there were significant correlation between acceptance and attitude toward LGBT community among college students and a significant relationship between acceptance and attitude based on gender among students. This also shows although government policies and laws relating to religion limit social, religious and gender equality in Malaysia, however at the college level, students are open, tolerant and accepting of these groups in the society. Therefore, it is recommended that further studies should be carried out among young people of various races, namely Malays, Chinese and Indians as the younger generation is more open-minded and provide services and facilities to better serve this group. In addition, the acceptance and attitudes of LGBT individuals attending primary and secondary schools should be helped to ensure that LGBT groups are not excluded from the national education system.